Investigating the Satisfaction of Professors and Students with the Use of Conventional and Digital Radiography in the Endodontics Department of Mashhad Dental School - Armita Rouhani; Neda Naghavi; Mohadeseh Pasandideh (Mashhad University of Medical Sciences, 2023)
Introduction: Digital radiography seems necessary for overcoming educational problems and archiving radiographs taken from patients; nonetheless, the views of students and professors about this issue have been less studied. Therefore, the present study aimed to investigate the satisfaction of professors and students with the use of conventional and digital radiography in the Endodontics Department of Mashhad Dental School.Materials and Methods: This study was conducted on the professors of the Department of Root Therapy and 155 Dental Students in Mashhad. The research tool consisted of two researcher-made questionnaires. The first questionnaire was about the quality of the root therapy that was completed by the professors. The second questionnaire was about students' satisfaction with the use of digital and conventional radiography in the endodontics section. The information was recorded, and the data were then compared using Chi-square and Fisher tests.Results: The findings of this study demonstrated that from professors' point of view, digital imaging in dentistry had better quality, shorter time, and less error, and professors' satisfaction was significantly higher. Moreover, students had a more positive opinion of digital imaging in terms of quality, less time, less error, and less student congestion. Finally, students were more satisfied with digital imaging (P=0.05).Conclusion: As evidenced by the obtained results, it can be concluded that digital radiography improved the education and satisfaction of both groups of students and professors.